1992
DOI: 10.1111/j.1365-313x.1992.tb00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a pollen‐specific cDNA from sunflower encoding a zinc finger protein

Abstract: We have isolated, via differential hybridization screening of a floral cDNA library from sunflower, a cDNA clone that hybridizes to a 1100 nucleotide-long mRNA found exclusively in mature pollen grains. The cDNA encodes a 219 amino acid-long polypeptide containing two potential zinc fingers alternating with two basic domains. A similar organization is found in the erythroid-specific transcription factor Eryf1 from chicken and its murine homolog GF-1. The C-terminus of the protein contains a sixfold repeat of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…the CRP family [Schmeichel and Beckerle, 1997;Grubinger and Gimona, 2004;Tran et al, 2005]). In flowering plants, several CRP-related LIM orthologs have been found in Arabidopsis, rice (Arnaud et al, 2007), tobacco , sunflower (Baltz et al, 1992), and lily pollen (this study). Although a few plant LIMs showed nuclear localization, such as NtWLIM1 (Thomas et al, 2006), LlLIM1 was seldom found in the vegetative nucleus of the pollen tube (data not shown).…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…the CRP family [Schmeichel and Beckerle, 1997;Grubinger and Gimona, 2004;Tran et al, 2005]). In flowering plants, several CRP-related LIM orthologs have been found in Arabidopsis, rice (Arnaud et al, 2007), tobacco , sunflower (Baltz et al, 1992), and lily pollen (this study). Although a few plant LIMs showed nuclear localization, such as NtWLIM1 (Thomas et al, 2006), LlLIM1 was seldom found in the vegetative nucleus of the pollen tube (data not shown).…”
mentioning
confidence: 58%
“…Amino acid sequence alignment analysis (Fig. 1B) showed that LlLIM1 shared high homology with other plant LIMs having two LIM domains, such as AtWLIM1, OsWLIM1 (Arnaud et al, 2007), HaWLIM1 (Baltz et al, 1992), and NtWLIM1 . In addition, for all plant LIMs examined, the tandem zinc finger motifs present in both LIM domains contained eight conserved Cys/His residues (Fig.…”
Section: Cloning and Characterization Of Lllim1 A Lily Lim Isoform Pmentioning
confidence: 99%
“…These protein-protein interactions are governed by a variety of protein binding domains one of which is the LIM domain. Since first described nearly 2 decades ago (21, 28, 57), LIM domain-containing proteins have been identified in a wide range of eukaryotes, including protozoa (16,30,45), plants (5,20,40), and yeast (Saccharomyces cerevisiae) (39), stressing the evolutionary importance of these proteins. In the parasitic protozoan Entamoeba histolytica, a few studies have revealed the presence of such proteins (17, 36), although to date, no LIM domain-containing proteins have been characterized in this organism.…”
mentioning
confidence: 99%
“…Since the available polyclonal anti-EPLIN antisera do not distinguish the two known isoforms of EPLIN, we carried out in situ immunouorescence using two dierent cell lines, HOK18C (an immortalized human oral keratinocyte line), and BeWo (a human choriocarcinoma cell line). EPLIN-a is expressed as the predominant form of HOK18C, (Nagase et al, 1998), plant transcription factor SF3 (Baltz et al, 1992), and muscle LIM protein (Arber et al, 1994) is shown. The signature cysteine and histidine residues of LIM domain are indicated by bold lettering.…”
mentioning
confidence: 99%